2001
DOI: 10.1177/144078301128756184
|View full text |Cite
|
Sign up to set email alerts
|

Where ‘angels’ and ‘wusses’ fear to tread: sexual coercion in adolescent dating relationships

Abstract: Sexual coercion of female adolescents is a major ongoing concern of feminists. This article provides a comparative analysis of a sample of New Zealand and British adolescents' narratives concerning sexuality, sexual practices and coercion within heterosexual dating relationships. The narratives suggest that sexual coercion operates through ‘normal’ heterosexuality which employs discursive dichotomies of femininity and masculinity. ‘Slut’/’angel’ and ‘wuss’/ ‘stud’ dichotomies provide an oversimplified grid fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 11 publications
7
80
0
Order By: Relevance
“…A narrative analysis of dating among heterosexual adolescents in New Zealand and England found that adolescents viewed the use of sexual coercion by males as a normal part of masculinity and heterosexual relations (Hird & Jackson, 2001). Other qualitative work has shown that women use the romantic narrative to justify and understand abuse in their relationships, defining themselves in light of the heteronormative model of femininity in which their job is to provide love and care to abusers with the hope of helping them (Jackson, 2001;Wood, 2001).…”
Section: Heteronormativity and Sexual Coercionmentioning
confidence: 99%
“…A narrative analysis of dating among heterosexual adolescents in New Zealand and England found that adolescents viewed the use of sexual coercion by males as a normal part of masculinity and heterosexual relations (Hird & Jackson, 2001). Other qualitative work has shown that women use the romantic narrative to justify and understand abuse in their relationships, defining themselves in light of the heteronormative model of femininity in which their job is to provide love and care to abusers with the hope of helping them (Jackson, 2001;Wood, 2001).…”
Section: Heteronormativity and Sexual Coercionmentioning
confidence: 99%
“…Often young women's sexuality is explored not as primary, but rather as a secondary desire, that is, as a response to men's sexuality (Hird & Jackson, 2001). The tendency for women to define their sexuality within the context of the intimate relationship, or as secondary to that of their male partners, means that the quality of interpersonal functioning within the relationship may directly serve to strengthen or undermine women's sexual self-perceptions.…”
Section: Women's Sexual Self-definitionsmentioning
confidence: 99%
“…In some African cultures, for instance, unquestioned authority is reposed in the male and the female is expected to acquiesce under all circumstances. It is normally viewed as disrespect when the female tries to stand for her right in relation to the male, (Akintunde et al, 2002), especially in the domestic setting and for many young people, sexual harassment and male aggression are normalized in that there is pressure among boys to behave in sexually aggressive ways while girls are compelled to accommodate males' needs and desires (Hird & Jackson, 2001; Tolman, Spencer, Rossen-Reynoso & Porche, 2003).In married life, the woman is seen not as an individual but, rather as a representation of various opinions formed from experiences of battered relationships seen in the family in the form of maltreatment, sexual abuse and economic abuse. All these experiences create some form of fear and inhibit the woman from expressing herself without fear or let (Akintunde et al, 2002).…”
Section: Background To the Studymentioning
confidence: 99%